2013
DOI: 10.1055/s-0032-1331812
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Ultrasound: Technique and Application

Abstract: Transcranial Doppler (TCD) ultrasound provides rapid, noninvasive, real-time measures of cerebrovascular function. TCD can be used to measure flow velocity in the basal arteries of the brain to assess relative changes in flow, diagnose focal vascular stenosis, or to detect embolic signals within these arteries. TCD can also be used to assess the physiologic health of a particular vascular territory by measuring blood flow responses to changes in blood pressure (cerebral autoregulation), changes in end-tidal CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
261
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(264 citation statements)
references
References 81 publications
0
261
0
3
Order By: Relevance
“…52,55,73,92,93 Lastly, often only the posterior window is suitable for insonating intracranial vessels in the elderly, due to skull thickening with advancing age. 94 Some studies have reported that 10À15% of individuals will have inadequate windows for insonating intracranial cerebral vessels; 95 as such, it may be advantageous to utilize other techniques such as NIRS (see next section) in addition to TCD for studies in the elderly or those with related cerebrovascular pathology.…”
Section: Transcranial Dopplermentioning
confidence: 99%
“…52,55,73,92,93 Lastly, often only the posterior window is suitable for insonating intracranial vessels in the elderly, due to skull thickening with advancing age. 94 Some studies have reported that 10À15% of individuals will have inadequate windows for insonating intracranial cerebral vessels; 95 as such, it may be advantageous to utilize other techniques such as NIRS (see next section) in addition to TCD for studies in the elderly or those with related cerebrovascular pathology.…”
Section: Transcranial Dopplermentioning
confidence: 99%
“…Microembolic signals (MESs) in patients with carotid stenosis, myocardial infarction, atrial fibrillation, and mechanical cardiac valves are often detectable in the cerebral circulation by a transcranial Doppler (TCD; Levi et al, 1997;Purkayastha and Sorond, 2012). Clinical evidence has demonstrated that the presence of MES in the cerebral circulation is an independent predictor of the risk and prognosis of stroke (Gao et al, 2004;Markus et al, 2005) and recurrence in patients with previous stroke or transient ischemic attack (TIA) of presumed arterial origin (Valton et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We chose Transcranial Doppler ultrasound (TCD) to monitor CBF changes because of its low cost, excellent temporal resolution and sensitivity to CBF changes within the circle of Willis and the large intracranial vessels, as shown in a variety of neurologic disorders (Purkayastha & Sorond, 2012). The variables we measured are commonly used to estimate cerebrovascular responsiveness to various stimuli (Watt, Burnfield, Truemper, Buster, & Bashford, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The variables we measured are commonly used to estimate cerebrovascular responsiveness to various stimuli (Watt, Burnfield, Truemper, Buster, & Bashford, 2012). In particular, one can estimate the distal cerebrovascular resistance by measuring the PI, which depends on multiple hemodynamic variables including the metabolic changes during cognitive tasks (thus being possible to indirectly estimate changes in brain metabolism) (D'Andrea et al., 2016; Demarin & Morovic, 2014; Kenney et al., 2016; Kim & Lee, 2015; Purkayastha & Sorond, 2012; Wolf, 2015). …”
Section: Introductionmentioning
confidence: 99%